The Whole Nature Of God In The Predestination Dilemma - Pangeran Manurung (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2019)
The problem in this paper lies in the polemic that arises in the understanding of double predestination, especially regarding the theological dilemmas in it. On the one hand, God is described as a cruel and inhuman God when only choosing some people to be saved, and on the other hand Christian doctrine recognizes that God does indeed choose some people to love. The purpose of writing this essay is to prove that a comprehensive approach can reduce theological dilemmas and conflicts when discussing the formulation of predestination. The research method used is literature study, by describing the core of Calvin's double predestination and reviewing it by involving the interrelated attributes of God. The results of this study prove that when the concept of predestination is reviewed by involving the attributes of God as a whole, it appears that God cannot be called an arrogant God when choosing humans in the project of salvation.